Product specialization: how different brands compete - Brookes, Maureen (Henry Stewart Talks, 2009)
Why brand?, What is a successful brand?, A distinctive identity, Brand personality and positioning, Building blocks of a brand, Hotel brand strategies, Brand architecture, Expansion by price points, Brand specialization by class, Branding in a hotel industry, Brand specialization, Brand proliferation